Problematizing consent: searching genetic genealogy databases for law enforcement purposes. Issue 3 (3rd July 2021) - Samuel, G.; Kennett, D.
Abstract : Genetic genealogy databases have become particularly attractive to law enforcement agencies, especially in the United States (US), which have started to employ genealogists to search them with unknown origin DNA from unidentified human remains (suicides, missing persons) or from a serious crime scene, to help identify the victim, or a potential suspected perpetrator, respectively . While this investigative genetic genealogy (IGG) technique holds much promise, its use – particularly during serious criminal investigations – has sparked a range of social and ethical concerns. Receiving consent for IGG from genetic genealogy database users has been argued as a way to address such concerns. While critiques of the importance of consent are well documented in the biomedical and forensic biobanking literature, this has not been explored for IGG. We sought to address this gap by exploring the views of UK stakeholders. Our research question was: what are UK public and professional stakeholders' views about the importance of the consent process for IGG when used for serious criminal cases? The methodological approach was interview-based and exploratory. Our analysis identified that all interviewees stressed the importance of consent, though interviewees' narratives pointed to inadequacies of individual-based consent as an ethical panacea for IGG.